Peran Supervisi Kepala Sekolah Terhadap Tugas Pokok Guru Pendidikan Agama Islam - Amelia Rasyid; Alfurqan Alfurqan; Edi Saputra (An-Nuha, 2022)
The purpose of the study to determine the role of the principal's supervision on the main tasks of Islamic religious education teachers at SMA N 10 Padang. This study uses a qualitative method. The data sources of this research were the principals and teachers of Islamic religious education at SMA N 10 Padang. The techniques used in this research are observation, interviews, and documentation. Data analysis was carried out through the stages of data reduction, data presentation, and drawing conclusions. The results of his research show that there are four supervisory roles of school principals in the main tasks of teachers of Islamic religious education at SMA N 10 Padang, including the following: the principal acts as Coordinator, Consultant, Group Leader, and Evaluator.